Improving the Students’ Self-confidence in Speaking English through YouTube - Tri Pujiani; Khoirun Nisa; Benny Krisbiantoro (Universitas 'Aisyiyah Yogyakarta, 2021)
Speaking in English is often a frightening spectre for students since it is complex and involves all language elements. Self-confidence is one of the factors that influencing speaking performance. The students’ self-confidence can be stimulated by using an interesting activity that promotes practice in relax situation. The use of social media such as YouTube may be the alternative to train the students’ self-confidence in speaking English. This research was aimed to improve the students’ self-confidence in order to overcome their problem in Speaking English by utilizing YouTube as the media. In this research, the students were assigned to post their speaking assignments on YouTube. This research was a quasi-experimental one group with pre and post-test research that utilized 43 students from English for Nursing 1 Class as the sample who were taken by using random sampling. The research data were obtained from the students’ verbal scores and self-confidence questionnaire which were compared before and after the project. The result of this research showed that there was an increase on the students’ self-confidence and speaking performance after they joined this project. Moreover, paired t-test proved that the increase was significant. Thus, it can be concluded that utilizing YouTube as the media to post the students’ work is effective to increase the students’ self-confidence as well as their speaking performance. This project should be continued and developed to maintain the students’ self-confidence and facilitate more practice for students in speaking English.